Volume 1A: Combustion, Fuels and Emissions 2013
DOI: 10.1115/gt2013-94782
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pressure and Steam Dilution on NOx and CO Emissions in a Premixed Natural Gas Flame

Abstract: In the current study, the influence of pressure and steam on the emission formation in a premixed natural gas flame is investigated at pressures between 1.5 bar and 9 bar. A premixed, swirl-stabilized combustor is developed that provides a stable flame up to very high steam contents. Combustion tests are conducted at different pressure levels for equivalence ratios from lean blowout to near-stoichiometric conditions and steam-to-air mass ratios from 0% to 25%. A reactor network is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…with p 0 being a reference pressure and α, the scaling exponent. This scaling law was shown to be applicable at steam diluted conditions [23].…”
Section: No X Emissionsmentioning
confidence: 86%
“…with p 0 being a reference pressure and α, the scaling exponent. This scaling law was shown to be applicable at steam diluted conditions [23].…”
Section: No X Emissionsmentioning
confidence: 86%
“…3, left panel). Given that the main sources of NO x emission, i.e., coal combustion from coal power plants, industrial manufacturing processes, fuel burning from motor vehicles, and natural gas burning (Göke et al, 2014), are relatively the same for all four seasons, the contribution of scattered coal heating or central heating boilers without denitrification devices to the increase of NO − 3 concentrations during winter cannot be ignored. The lower height of the planetary boundary layer during the winter is another reason for the high concentrations during winter.…”
Section: Winter Concentrations and Year-long Aerosol Pollutionmentioning
confidence: 99%
“…A CCD camera (D70s, Nikon, Tokyo, Japan) equipped with an AF Nikkor lens (50 mm/F1.8D, Nikon, Tokyo, Japan) and a band-pass CH filter (430/10, LaVision, Göttingen, Germany) was used to record the time-averaged CH chemiluminescence images for CH 4 /air and CH 4 /air/steam flames. All the images were recorded with an exposure time of 0.77 s and a resolution of 3008 × 2000 pixels.…”
Section: Flame Visualization With the Ch Chemiluminescence Imagingmentioning
confidence: 99%
“…Kuhn et al studied the influence of steam addition with different fuels, and they found that, in order to prevent lean blowout event, higher equivalence ratios are required with increasing steam addition [18]. Göke et al [4] studied the steam influence with a premixed natural gas flame at different pressures. Their results indicated that the higher steam to air mass ratio leads to a higher blowout equivalence ratio, and no stable flame was achieved above a maximum steam to air mass ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation